Design and Optimization of an Ultra-Low-Power Cross-Coupled LC VCO with a DFF Frequency Divider for 2.4 GHz RF Receivers Using 65 nm CMOS Technology - Muhammad Faisal Siddiqui; Mukesh Kumar Maheshwari; Muhammad Raza; Aurangzeb Rashid Masud (Journal of Low Power Electronics and Applications, 2023)
This article presents the design and optimization of a tunable quadrature differential LC CMOS voltage-controlled oscillator (VCO) with a D flip-flop (DFF) frequency divider. The VCO is designed for the low-power and low-phase-noise applications of 2.4 GHz IoT/BLE receivers and wireless sensor devices. The proposed design comprises the proper stacking of an LC VCO and a DFF frequency divider and is simulated using a TSMC 65 nm CMOS technology, and it has a tuning range of 4.4 to 5.7 GHz. The voltage headroom is preserved using a high-impedance on-chip passive inductor at the tail for filtering and enabling true differential operation. The VCO and frequency divider consume as low as 2.02 mW altogether, with the VCO section consuming only 0.47 mW. The active area of the chip including the pads is only 0.47 mm2. The designed VCO achieved a much better phase noise of −118.36 dBc/Hz at a 1 MHz offset frequency with 1.2 V supply voltages. The design produced a much better FoM of −196.44 dBc/Hz compared to other related research.